Stability and Control of the Money Supply - Brito, D. L.; Hester, Donald D. (Quarterly Journal of Economics, 1974)
I. The state variables: balance sheets and information, 279. — II. The model, 284. — III. Numerical illustrations of monetary control, 290. — IV. Conclusions, 301. — Appendix: Derivation of Figure I, 303.